Improving the Quality of Teaching. The Best of ERIC on Educational Management, No. 90 - ERIC Clearinghouse on Educational Management, Eugene, OR.; ERIC Clearinghouse on Educational Management (Eugene, OR : ERIC Clearinghouse on Educational Management, 1987)
The 11 journal articles reviewed in this annotated bibliography focus on ways teachers and principals can improve the quality of teaching. Among the four articles directed toward principals are two that relate to the culture of the school; another presents a model to principals for achieving quality instruction; and the fourth proposes six strategies principals can use in classroom observation. Articles directed toward teachers describe: (1) a self-assessment procedure to help teachers and supervisors improve instructional effectiveness; (2) a teacher-directed, mastery learning approach used by the Exemplary Center for Reading Instruction (ECRI); (3) strategies that teachers can use to expand student thinking capability; and (4) a mastery learning program for teachers. Research applications are discussed in two articles: one reviews six paradigms of classroom research that have helped define the concept of effective teaching; the other, citing views of teaching as both a science and an art, deals with the difficulty in assessing teacher effectiveness through conventional research methods. The final article explores the six common factors of the Instructionally Effective Schools approach as a way to improve education without additional funding. (MLF)
Availability: Publication Sales, ERIC Clearinghouse on Educational Management, University of Oregon, 1787 Agate Street, Eugene, OR 97403 (free).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: 400-86-0003.
Administrators.
Teachers.
Practitioners.
Keywords: Administrator Role; Classroom Observation Techniques; Classroom Research; Classroom Techniques; Elementary Secondary Education; Instructional Effectiveness; Instructional Leadership; Literature Reviews; Mastery Learning; Principals; Self Evaluation (Individuals); Staff Development; Teacher Effectiveness; Teacher Improvement; ERIC Publications; Reference Materials, Bibliographies